Comparison between Under-13 and Under-15 Soccer Players in Small-Sided and Conditioned Games - Silva, Davi Correia da (2020)
The present study aims to compare players' tactical behavior and performance in Small-Sided and Conditioned Games when playing against opponents from different age levels (Under-13 and Under-15). Participated in this study 93 players from U-13 (n=42) and U-15 (n=51) teams, who performed 7,416 tactical actions. The instrument used was the System of Tactical Assessment in Soccer (FUT-SAT) to analyze players' tactical actions. Descriptive statistics and independent t-tests and Mann-Whitney were used considering the value of p<0.05. Results indicated that the players in the U-13 age level obtained a better percentage of success in the movements supporting the player in possession of the ball, and the U-15 players performed more movements that allow the team to defend in unity. In addition, players of both age levels performed similarly, although U-13 players suffered more fouls and won more throw-ins or corner kicks, whereas the U-15 age level was more effective in regaining possession of the ball but suffered fewer attacks to their goal. It was concluded that the players of the U-15 age are more compacted compared to the U-13 players. Besides, both age performances were similar even though the players of the U-15 age level were more effective.